Bernoulli and Euler Polynomials - 25.2 Definition and Expansions

From testwiki
Revision as of 12:03, 28 June 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
25.2.E1 ζ ( s ) = n = 1 1 n s Riemann-zeta 𝑠 superscript subscript 𝑛 1 1 superscript 𝑛 𝑠 {\displaystyle{\displaystyle\zeta\left(s\right)=\sum_{n=1}^{\infty}\frac{1}{n^% {s}}}}
\Riemannzeta@{s} = \sum_{n=1}^{\infty}\frac{1}{n^{s}}

Zeta(s) = sum((1)/((n)^(s)), n = 1..infinity)
Zeta[s] == Sum[Divide[1,(n)^(s)], {n, 1, Infinity}, GenerateConditions->None]
Failure Successful
Failed [4 / 6]
Result: Float(-infinity)
Test Values: {s = -3/2}

Result: Float(-infinity)
Test Values: {s = -1/2}

... skip entries to safe data
Successful [Tested: 6]
25.2.E2 ζ ( s ) = 1 1 - 2 - s n = 0 1 ( 2 n + 1 ) s Riemann-zeta 𝑠 1 1 superscript 2 𝑠 superscript subscript 𝑛 0 1 superscript 2 𝑛 1 𝑠 {\displaystyle{\displaystyle\zeta\left(s\right)=\frac{1}{1-2^{-s}}\sum_{n=0}^{% \infty}\frac{1}{(2n+1)^{s}}}}
\Riemannzeta@{s} = \frac{1}{1-2^{-s}}\sum_{n=0}^{\infty}\frac{1}{(2n+1)^{s}}
s > 1 𝑠 1 {\displaystyle{\displaystyle\Re s>1}}
Zeta(s) = (1)/(1 - (2)^(- s))*sum((1)/((2*n + 1)^(s)), n = 0..infinity)
Zeta[s] == Divide[1,1 - (2)^(- s)]*Sum[Divide[1,(2*n + 1)^(s)], {n, 0, Infinity}, GenerateConditions->None]
Successful Successful - Successful [Tested: 2]
25.2.E3 ζ ( s ) = 1 1 - 2 1 - s n = 1 ( - 1 ) n - 1 n s Riemann-zeta 𝑠 1 1 superscript 2 1 𝑠 superscript subscript 𝑛 1 superscript 1 𝑛 1 superscript 𝑛 𝑠 {\displaystyle{\displaystyle\zeta\left(s\right)=\frac{1}{1-2^{1-s}}\sum_{n=1}^% {\infty}\frac{(-1)^{n-1}}{n^{s}}}}
\Riemannzeta@{s} = \frac{1}{1-2^{1-s}}\sum_{n=1}^{\infty}\frac{(-1)^{n-1}}{n^{s}}
s > 0 𝑠 0 {\displaystyle{\displaystyle\Re s>0}}
Zeta(s) = (1)/(1 - (2)^(1 - s))*sum(((- 1)^(n - 1))/((n)^(s)), n = 1..infinity)
Zeta[s] == Divide[1,1 - (2)^(1 - s)]*Sum[Divide[(- 1)^(n - 1),(n)^(s)], {n, 1, Infinity}, GenerateConditions->None]
Failure Successful Successful [Tested: 3] Successful [Tested: 3]
25.2.E4 ζ ( s ) = 1 s - 1 + n = 0 ( - 1 ) n n ! γ n ( s - 1 ) n Riemann-zeta 𝑠 1 𝑠 1 superscript subscript 𝑛 0 superscript 1 𝑛 𝑛 Stieltjes-constants 𝑛 superscript 𝑠 1 𝑛 {\displaystyle{\displaystyle\zeta\left(s\right)=\frac{1}{s-1}+\sum_{n=0}^{% \infty}\frac{(-1)^{n}}{n!}\gamma_{n}(s-1)^{n}}}
\Riemannzeta@{s} = \frac{1}{s-1}+\sum_{n=0}^{\infty}\frac{(-1)^{n}}{n!}\StieltjesConstants{n}(s-1)^{n}

Zeta(s) = (1)/(s - 1)+ sum(((- 1)^(n))/(factorial(n))*gamma(n)*(s - 1)^(n), n = 0..infinity)
Error
Failure Missing Macro Error Successful [Tested: 6] -
25.2.E5 γ n = lim m ( k = 1 m ( ln k ) n k - ( ln m ) n + 1 n + 1 ) Stieltjes-constants 𝑛 subscript 𝑚 superscript subscript 𝑘 1 𝑚 superscript 𝑘 𝑛 𝑘 superscript 𝑚 𝑛 1 𝑛 1 {\displaystyle{\displaystyle\gamma_{n}=\lim_{m\to\infty}\left(\sum_{k=1}^{m}% \frac{(\ln k)^{n}}{k}-\frac{(\ln m)^{n+1}}{n+1}\right)}}
\StieltjesConstants{n} = \lim_{m\to\infty}\left(\sum_{k=1}^{m}\frac{(\ln@@{k})^{n}}{k}-\frac{(\ln@@{m})^{n+1}}{n+1}\right)

gamma(n) = limit(sum(((ln(k))^(n))/(k), k = 1..m)-((ln(m))^(n + 1))/(n + 1), m = infinity)
Error
Successful Missing Macro Error - -
25.2.E6 ζ ( s ) = - n = 2 ( ln n ) n - s diffop Riemann-zeta 1 𝑠 superscript subscript 𝑛 2 𝑛 superscript 𝑛 𝑠 {\displaystyle{\displaystyle\zeta'\left(s\right)=-\sum_{n=2}^{\infty}(\ln n)n^% {-s}}}
\Riemannzeta'@{s} = -\sum_{n=2}^{\infty}(\ln@@{n})n^{-s}
s > 1 𝑠 1 {\displaystyle{\displaystyle\Re s>1}}
diff( Zeta(s), s$(1) ) = - sum((ln(n))*(n)^(- s), n = 2..infinity)
D[Zeta[s], {s, 1}] == - Sum[(Log[n])*(n)^(- s), {n, 2, Infinity}, GenerateConditions->None]
Successful Successful - Successful [Tested: 2]
25.2.E7 ζ ( k ) ( s ) = ( - 1 ) k n = 2 ( ln n ) k n - s Riemann-zeta 𝑘 𝑠 superscript 1 𝑘 superscript subscript 𝑛 2 superscript 𝑛 𝑘 superscript 𝑛 𝑠 {\displaystyle{\displaystyle{\zeta^{(k)}}\left(s\right)=(-1)^{k}\sum_{n=2}^{% \infty}(\ln n)^{k}n^{-s}}}
\Riemannzeta^{(k)}@{s} = (-1)^{k}\sum_{n=2}^{\infty}(\ln@@{n})^{k}n^{-s}
s > 1 𝑠 1 {\displaystyle{\displaystyle\Re s>1}}
diff( Zeta(s), s$(k) ) = (- 1)^(k)* sum((ln(n))^(k)* (n)^(- s), n = 2..infinity)
D[Zeta[s], {s, k}] == (- 1)^(k)* Sum[(Log[n])^(k)* (n)^(- s), {n, 2, Infinity}, GenerateConditions->None]
Failure Failure Successful [Tested: 2] Successful [Tested: 2]
25.2.E8 ζ ( s ) = k = 1 N 1 k s + N 1 - s s - 1 - s N x - x x s + 1 d x Riemann-zeta 𝑠 superscript subscript 𝑘 1 𝑁 1 superscript 𝑘 𝑠 superscript 𝑁 1 𝑠 𝑠 1 𝑠 superscript subscript 𝑁 𝑥 𝑥 superscript 𝑥 𝑠 1 𝑥 {\displaystyle{\displaystyle\zeta\left(s\right)=\sum_{k=1}^{N}\frac{1}{k^{s}}+% \frac{N^{1-s}}{s-1}-s\int_{N}^{\infty}\frac{x-\left\lfloor x\right\rfloor}{x^{% s+1}}\mathrm{d}x}}
\Riemannzeta@{s} = \sum_{k=1}^{N}\frac{1}{k^{s}}+\frac{N^{1-s}}{s-1}-s\int_{N}^{\infty}\frac{x-\floor{x}}{x^{s+1}}\diff{x}
s > 0 𝑠 0 {\displaystyle{\displaystyle\Re s>0}}
Zeta(s) = sum((1)/((k)^(s)), k = 1..N)+((N)^(1 - s))/(s - 1)- s*int((x - floor(x))/((x)^(s + 1)), x = N..infinity)
Zeta[s] == Sum[Divide[1,(k)^(s)], {k, 1, N}, GenerateConditions->None]+Divide[(N)^(1 - s),s - 1]- s*Integrate[Divide[x - Floor[x],(x)^(s + 1)], {x, N, Infinity}, GenerateConditions->None]
Failure Aborted
Failed [3 / 3]
Result: .2180864797
Test Values: {s = 3/2, N = 3}

Result: Float(infinity)
Test Values: {s = 1/2, N = 3}

... skip entries to safe data
Skipped - Because timed out
25.2.E11 ζ ( s ) = p ( 1 - p - s ) - 1 Riemann-zeta 𝑠 subscript product 𝑝 superscript 1 superscript 𝑝 𝑠 1 {\displaystyle{\displaystyle\zeta\left(s\right)=\prod_{p}(1-p^{-s})^{-1}}}
\Riemannzeta@{s} = \prod_{p}(1-p^{-s})^{-1}
s > 1 𝑠 1 {\displaystyle{\displaystyle\Re s>1}}
Zeta(s) = product((1 - (p)^(- s))^(- 1), p = - infinity..infinity)
Zeta[s] == Product[(1 - (p)^(- s))^(- 1), {p, - Infinity, Infinity}, GenerateConditions->None]
Failure Failure Error
Failed [2 / 2]
Result: Plus[2.612375348685488, Times[-1.0, NProduct[Power[Plus[1, Times[-1, Power[p, -1.5]]], -1]
Test Values: {p, DirectedInfinity[-1], DirectedInfinity[1]}, Rule[GenerateConditions, None]]]], {Rule[s, 1.5]}

Result: Plus[1.6449340668482262, Times[-1.0, NProduct[Power[Plus[1, Times[-1, Power[p, -2]]], -1]
Test Values: {p, DirectedInfinity[-1], DirectedInfinity[1]}, Rule[GenerateConditions, None]]]], {Rule[s, 2]}

25.2.E12 ζ ( s ) = ( 2 π ) s e - s - ( γ s / 2 ) 2 ( s - 1 ) Γ ( 1 2 s + 1 ) ρ ( 1 - s ρ ) e s / ρ Riemann-zeta 𝑠 superscript 2 𝜋 𝑠 superscript 𝑒 𝑠 𝑠 2 2 𝑠 1 Euler-Gamma 1 2 𝑠 1 subscript product 𝜌 1 𝑠 𝜌 superscript 𝑒 𝑠 𝜌 {\displaystyle{\displaystyle\zeta\left(s\right)=\frac{(2\pi)^{s}e^{-s-(\gamma s% /2)}}{2(s-1)\Gamma\left(\tfrac{1}{2}s+1\right)}\prod_{\rho}\left(1-\frac{s}{% \rho}\right)e^{s/\rho}}}
\Riemannzeta@{s} = \frac{(2\pi)^{s}e^{-s-(\EulerConstant s/2)}}{2(s-1)\EulerGamma@{\tfrac{1}{2}s+1}}\prod_{\rho}\left(1-\frac{s}{\rho}\right)e^{s/\rho}
( 1 2 s + 1 ) > 0 1 2 𝑠 1 0 {\displaystyle{\displaystyle\Re(\tfrac{1}{2}s+1)>0}}
Zeta(s) = ((2*Pi)^(s)* exp(- s -(gamma*s/2)))/(2*(s - 1)*GAMMA((1)/(2)*s + 1))*product((1 -(s)/(rho))*exp(s/rho), rho = - infinity..infinity)
Zeta[s] == Divide[(2*Pi)^(s)* Exp[- s -(EulerGamma*s/2)],2*(s - 1)*Gamma[Divide[1,2]*s + 1]]*Product[(1 -Divide[s,\[Rho]])*Exp[s/\[Rho]], {\[Rho], - Infinity, Infinity}, GenerateConditions->None]
Failure Failure Error
Failed [5 / 5]
Result: Plus[Complex[-0.02548520188983307, 3.121037092000815*^-18], Times[0.02420092827533985, NProduct[Times[Power[E, Times[-1.5, Power[ρ, -1]]], Plus[1, Times[1.5, Power[ρ, -1]]]]
Test Values: {ρ, DirectedInfinity[-1], DirectedInfinity[1]}, Rule[GenerateConditions, None]]]], {Rule[s, -1.5]}

Result: Plus[2.612375348685488, Times[-2.4801151038890965, NProduct[Times[Power[E, Times[1.5, Power[ρ, -1]]], Plus[1, Times[-1.5, Power[ρ, -1]]]]
Test Values: {ρ, DirectedInfinity[-1], DirectedInfinity[1]}, Rule[GenerateConditions, None]]]], {Rule[s, 1.5]}

... skip entries to safe data